Employment the Laser to Fabricate the Surface Plasmon Resonance Sensor - Alalak, Tamara; Y. Hammod, Haider (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
The Optical Fiber sensor based on the Surface Plasmon Resonance (SPR) technology hasbeen a successful performance sensing and presents high sensitivity. This thesis investigates theperformance of several structure of SPR sensor in field of refractive index and chemicalapplications. A structure of Multi-Mode Fiber- Single Mode Fiber- Multi Mode Fiber (MMFSMF-MMF)